Substitution for Substitution in Measure for Measure - Anton Schütz; Chantal Schütz (Sillages Critiques)
Is Measure for Measure “Shakespeare’s play on law”, as it is often asserted?  Law appears together with religion and politics as one combined powerful normative order. The judge’s power is shaped, not in terms of the adversarial trial of the common law, but in those of the continental inquisitorial one. At the heart of the play we find, this too has frequently been pointed out, the theme of substitution: Angelo substitutes for the Duke, Mariana for Isabella, Ragozine’s head for Claudio’s, the friar for the Duke, the Duke for the friar. Angelo’s jurisdiction provides a specific rule with total and immediate application, substituting for its previous long-term abeyance under the Duke’s. Is Shakespeare’s Angelo also, and perhaps primarily, a substitute for the holder of the absolute and yet ordinate power ascribed to God by another friar, John Duns Scotus (1265-1308), in whose theology the angels play such an important role, and of whose doctrine we know that it was to flourish in England for many centuries to come?